Task-Based Language Learning and Beginning Language Learners: Examining Classroom-Based Small Group Learning in Grade 1 French Immersion - Bourgoin, Renée; Le Bouthillier, Josée (Canadian Journal of Applied Linguistics, 2021)
Elementary French immersion (FI) language arts teachers often organize instruction around small learning groups. Students rotate through learning stations/centres and work independently with their peers on L2 literacy skills. This study examined how principles of task-based language teaching (TBLT) can be used and/or adapted to further support beginning L2 learners working independently at various literacy stations. This classroom-based study employed a pragmatic ‘research design’ methodology. Researchers worked alongside Grade 1 FI teachers (n=3) in the development and classroom implementation of language/literacy tasks designed around TBLT principles for use in literacy centres. Data collected included classroom observations in two Grade 1 FI classrooms, samples of students’ work, teacher interviews, and task-based lesson plans. Findings suggest that integrating/adapting TBLT principles to small group independent learning stations was particularly impactful in supporting young beginning language learners with extended language output, peer interaction, learner autonomy, emerging spontaneous language use, and student engagement. Additional instructional focus on corrective feedback, oral communication skills, and focus on form and function were also reported.